Visions of Contempt: Emotion and the Visual Culture of the Scopes Trial. (15th March 2022) - Schaefer, Donovan
Abstract: This article examines the visual culture of the 1925 Scopes Trial, including editorial cartoons from contemporary periodicals and the 1960 film version of Inherit the Wind. Combining studies of material religion with affect theory, it suggests that this network of imagery instantiates an "economy of dignity" in which different factions seek to consolidate their positions through visual representations of shame and pride. Content Warning: This article contains racist imagery.